Tet-Transgenic Rodents: a comprehensive, up-to date database - Schönig, Kai; Freundlieb, Sabine; Gossen, Manfred (Transgenic research, 2013)
Here we introduce the “Tet-Transgenic Rodents” database, documenting most of the published Tet-transgenic mouse lines generated in the past 2 decades. Aside from the >500 mouse lines listed, it also includes the first of the recently reported Tet-transgenic rat models. Since the Tet technology comprises two essential components, a cis-acting promoter (Ptet) and a trans-acting transactivator, the database has been organized accordingly. One section of the database summarizes the different transgenic mouse lines carrying mostly tissue specific promoters driving the Tet transactivator. Another section covers transgenic mouse lines carrying responder transgenes under Ptet control. The few existing rat transgenic lines are listed correspondingly. It is the purpose of this database to facilitate the repeated use of preexisting, validated transgenic lines as a shortcut for further research.
Gesehen am 26.07.2018
Published online: 23 November 2012